2011
DOI: 10.1111/j.2042-7158.2011.01420.x
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo laxative and toxicological evaluation and in-vitro antitumour effects of Mitracarpus frigidus aerial parts

Abstract: MFM showed significant antitumour activity for leukaemic cells. Moreover, it presented laxative potential and no in-vivo toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The methanolic extract of aerial parts (MFM) revealed the presence of flavonoids, tannins, alkaloids, terpenes, and quinones and showed antimicrobial, leishmanicidal, cytotoxic, and laxative activities. Moreover, MFM revealed no toxicity signs in rat models [22, 23]. Recently, the pyranonaphthoquinone psychorubrin was firstly isolated from this species [24].…”
Section: Introductionmentioning
confidence: 99%
“…The methanolic extract of aerial parts (MFM) revealed the presence of flavonoids, tannins, alkaloids, terpenes, and quinones and showed antimicrobial, leishmanicidal, cytotoxic, and laxative activities. Moreover, MFM revealed no toxicity signs in rat models [22, 23]. Recently, the pyranonaphthoquinone psychorubrin was firstly isolated from this species [24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the pyranonaphthoquinone psychorubrin was first isolated from this extract [8]. Moreover, MFM revealed no toxicity signs in rat models [7]…”
Section: Introductionmentioning
confidence: 99%
“…[5] Previous studies showed that the methanolic extract obtained from this plant (MFM) revealed the presence of flavonoids, tannins, alkaloids, terpenes and quinones, and presented antimicrobial, leishmanicidal, cytotoxic and laxative activities. [6,7] Recently, the pyranonaphthoquinone psychorubrin was first isolated from this extract. [8] Moreover, MFM revealed no toxicity signs in rat models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation